2020
DOI: 10.1002/ptr.6801
|View full text |Cite
|
Sign up to set email alerts
|

Saponins derived from the stems and leaves of Panax ginseng attenuate scrotal heat‐induced spermatogenic damage via inhibiting the MAPK mediated oxidative stress and apoptosis in mice

Abstract: Heat stress (HS) reaction is a stress response caused by adverse conditions. Currently, the incidence of reproductive malignancies particularly in males has been constantly increasing. This work investigated the effects of saponins derived from the stems and leaves of Panax ginseng (GSLS) on testicular injury induced by scrotal hyperthermia in mice. GSLS (150, 300 mg/kg) were administered intragastrically to mice for 14 days, then exposed to a single scrotal heat treatment at 43°C for 18 min on seventh day. HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 67 publications
(89 reference statements)
1
14
0
Order By: Relevance
“…al., 2022). When a large amount of ROS accumulated it increased mitochondrial permeability, stimulated proapoptotic factor release and initiated apoptosis(Liu et al, 2021). Consistently, this study indicated that Hoechst 33258 staining and western blot analysis to further detect apoptosis both in mice and in IEC-6 cells.…”
supporting
confidence: 79%
“…al., 2022). When a large amount of ROS accumulated it increased mitochondrial permeability, stimulated proapoptotic factor release and initiated apoptosis(Liu et al, 2021). Consistently, this study indicated that Hoechst 33258 staining and western blot analysis to further detect apoptosis both in mice and in IEC-6 cells.…”
supporting
confidence: 79%
“…Our current research found that the serum HSP70 level was increased during HS exposure. In previous studies, HS led to a significant increase in the expression of HSP70 protein levels in testicular tissue [ 42 ] and liver tissue of mice [ 43 ]. Interestingly, the administration of MCE to heat-stressed mice reduced the HSP70 level, which is identical to the findings in sows and IUGR piglets [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, H 2 O 2 combined with overexpression of PAGE4 weakened the activation of JNK1/2 and enhanced the activation of ERK1/2. It is speculated that oxidative stress induces cell death partly through activating the JNK pathway which has been known to be able to trigger an apoptotic cascade [ 38 , 39 ]. In contrast, the ERK pathway that promotes cell survival is also activated under OS, acting in conjunction with the JNK pathway to balance cell death [ 40 ].…”
Section: Discussionmentioning
confidence: 99%